2021
DOI: 10.1007/s40843-020-1630-2
|View full text |Cite
|
Sign up to set email alerts
|

A core-shell catalyst design boosts the performance of photothermal reverse water gas shift catalysis

Abstract: Photothermal reverse water gas shift (RWGS) catalysis holds promise for efficient conversions of greenhouse gas CO 2 and renewable H 2 , powered solely by sunlight, into CO, an important feedstock for the chemical industry. However, the performance of photothermal RWGS catalysis over existing supported catalysts is limited by the balance between the catalyst loading and dispersity, as well as stability against sintering. Herein, we report a core-shell strategy for the design of photothermal catalysts, by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The reverse water–gas shift (RWGS) reaction, a well-known CO 2 utilization reaction for carbon capture, utilization, and storage technologies, is critical to the overall CO 2 hydrogenation performance as it is the initial step of CO 2 hydrogenation, and a variety of subsequent products are derived based on the RWGS + X (e.g., CO hydrogenation) pathway. , For this process, the introduction of light elements has also been demonstrated to significantly enhance the catalytic performance. It is found that the product selectivity of Ni-based catalysts could be shifted from CH 4 to CO due to the introduction of P. , Moreover, Mo 2 C and Fe 2 C 5 catalysts are also used in the RWGS reaction and show excellent catalytic performance. , However, the origin of the interstitial light element-promoted RWGS process still remains unclear. It also encourages us to further explore the changes in structure–activity relationships due to the introduction of interstitial light elements and thus obtain the fundamental understanding for the RWGS process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reverse water–gas shift (RWGS) reaction, a well-known CO 2 utilization reaction for carbon capture, utilization, and storage technologies, is critical to the overall CO 2 hydrogenation performance as it is the initial step of CO 2 hydrogenation, and a variety of subsequent products are derived based on the RWGS + X (e.g., CO hydrogenation) pathway. , For this process, the introduction of light elements has also been demonstrated to significantly enhance the catalytic performance. It is found that the product selectivity of Ni-based catalysts could be shifted from CH 4 to CO due to the introduction of P. , Moreover, Mo 2 C and Fe 2 C 5 catalysts are also used in the RWGS reaction and show excellent catalytic performance. , However, the origin of the interstitial light element-promoted RWGS process still remains unclear. It also encourages us to further explore the changes in structure–activity relationships due to the introduction of interstitial light elements and thus obtain the fundamental understanding for the RWGS process.…”
Section: Introductionmentioning
confidence: 99%
“…35,37−40 For this process, the introduction of light elements has also been demonstrated to significantly enhance the catalytic performance. It is found that the product selectivity of Ni-based catalysts could be shifted from CH 4 to CO due to the introduction of P. 41,42 Moreover, Mo 2 C and Fe 2 C 5 catalysts are also used in the RWGS reaction and show excellent catalytic performance. 15,43 However, the origin of the interstitial light element-promoted RWGS process still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…S15†) to improve the activity and durability of the catalysts under more intense light. 34,35 This work reveals the importance of optimizing the dispersion of active sites via structural engineering and improving the photothermal conversion of the system via thermal management for enhanced photothermal catalytic performance. The general strategy can be extended to other nanoarray catalysts, laying a foundation for efficient photothermal catalytic CO 2 reduction.…”
Section: Discussionmentioning
confidence: 98%
“…20 Therefore, the solution to thermostability of adopted catalysts for high-temperature photothermal RWGS reaction is a great challenge. The intensively-adopted modifications to enhance the thermostability of catalysts, such as adding precious metal [21][22][23][24] or constructing core/shell structure, 25,26 are expensive or/and complex synthesis-invovled, which is difficult to apply in industry. Herein, we demonstrate an in-situ photothermal synthesis to obtain CuO x &FeO y catalyst with layered double hydroxides-derived pore-confined frame, which prevents the growing of CuO x and FeO y nanoparticles during hightemperature reaction, and the basic groups on the catalyst promote adsorption and activation of CO 2 .…”
Section: Introductionmentioning
confidence: 99%